Diagnosis of vestibular schwannoma in modern clinical practice - Małgorzata Żebrowska; Adam Nawrocki; Andrzej Kucharski; Michał Konopelko; Piotr Trojanowski; Janusz Klatka (Kazimierz Wielki University, 2019)
The auditory nerve tumor is the most common tumor of the cerebellopontine angle region (CPA). The use of modern diagnostic methods allows to detect the tumor at an early stage of development, and consequently, the possibility of effective treatment. The clinical features and the most effective diagnostic procedures are presented.